Respiratory depression and brain hypoxia induced by opioid drugs: morphine, oxycodone, heroin, and fentanyl - Kiyatkin, Eugene A. (Neuropharmacology, 2019)
Opioid drugs are important tools to alleviate pain of different origins, but they have strong addictive potential and their abuse at higher doses often results in serious health complications. Respiratory depression that leads to brain hypoxia is perhaps the most dangerous symptom of acute intoxication with opioids, and it could result in lethality. The development of substrate-specific sensors coupled with amperometry made it possible to directly evaluate physiological and drug-induced fluctuations in brain oxygen levels in awake, freely-moving rats. The goal of this review paper is to consider changes in brain oxygen levels induced by several opioid drugs (heroin, fentanyl, oxycodone, morphine). While some of these drugs are widely used in clinical practice, they all are abused, often at doses exceeding the clinical range and often resulting in serious health complications. First, we consider some basic knowledge regarding brain oxygen, its physiological fluctuations, and mechanisms involved in regulating its entry into brain tissue. Then, we present and discuss data on brain oxygen changes induced by each opioid drug within a wide range of doses, from low, behaviorally relevant, to high, likely to be self-administered by drug users. These data allowed us to compare the effects of these drugs on brain oxygen in terms of their potency, time-course, and their potential danger when used at high doses via rapid-onset administration routes. While most data discussed in this work were obtained in rats, we believe that these data have clear human relevance in addressing the alarming rise in lethality associated with the opioid abuse.